Metal bashing: iron deficiency and manganese overexposure impact on peripheral nerves. Issue 2 (17th January 2019) - Amos-Kroohs, Robyn M.; Usach, Vanina; Piñero, Gonzalo; Vorhees, Charles V.; Martinez Vivot, Rocío; Soto, Paula A.; Williams, Michael T.; Setton-Avruj, Patricia
ABSTRACT: Iron (Fe) deficiency (FeD) and manganese (Mn) overexposure (MnOE) may result in several neurological alterations in the nervous system. Iron deficiency produces unique neurological deficits due to its elemental role in central nervous system (CNS) development and myelination, which might persist after normalization of Fe in the diet. Conversely, MnOE is associated with diverse neurocognitive deficits. Despite these well-known neurotoxic effects on the CNS, the influence of FeD and MnOE on the peripheral nervous system (PNS) remains poorly understood. The aim of the present investigation was to examine the effects of developmental FeD and MnOE or their combination on the sciatic nerve of young and adult rats. The parameters measured included divalent metal transporter 1 (DMT1), transferrin receptor (TfR), myelin basic protein (MBP) and peripheral myelin protein 22 (PMP22) expression, as well as Fe levels in the nerve. Our results showed that FeD produced a significant reduction in MBP and PMP22 content at P29, which persisted at P60 after Fe-sufficient diet replenishment regardless of Mn exposure levels. At P60 MnOE significantly increased sciatic nerve Fe content and DMT1 expression. However, the combination of FeD and MnOE produced no marked motor skill impairment. Evidence indicates that FeD appears to hinder developmental peripheral myelination, while MnOE may directly alter Fe homeostasis. Further studies are required to elucidate the interplay between these pathological conditions.